Characterization of intercellular communication and mitochondrial donation by mesenchymal stromal cells derived from the human lung. Issue 1 (December 2016) - Sinclair, Kenneth; Yerkovich, Stephanie; Hopkins, Peter; Chambers, Daniel
Abstract Background Bone marrow-derived mesenchymal stromal cells (BM-MSCs) are capable of repairing wounded lung epithelial cells by donating cytoplasmic material and mitochondria. Recently, we characterized two populations of human lung-derived mesenchymal stromal cells isolated from digested parenchymal lung tissue (LT-MSCs) from healthy individuals or from lung transplant recipients' bronchoalveolar lavage fluid (BAL-MSCs). The aim of this study was to determine whether LT-MSCs and BAL-MSCs are also capable of donating cytoplasmic content and mitochondria to lung epithelial cells. Methods Cytoplasmic and mitochondrial transfer was assessed by co-culturing BEAS2B epithelial cells with Calcein AM or Mitotracker Green FM-labelled MSCs. Transfer was then measured by flow cytometry and validated by fluorescent microscopy. Molecular inhibitors were used to determine the contribution of microtubules/tunnelling nanotubes (TNTs, cytochalasin D), gap junctions (carbenoxolone), connexin-43 (gap26) and microvesicles (dynasore). Results F-actin microtubules/TNTs extending from BM-MSCs, LT-MSCs and BAL-MSCs to bronchial epithelial cells formed within 45 minutes of co-culturing cells. Each MSC population transferred a similar volume of cytoplasmic content to epithelial cells. Inhibiting microtubule/TNTs, gap junction formation and microvesicle endocytosis abrogated the transfer of cytoplasmic material from BM-MSCs, LT-MSCs and BAL-MSCs to epithelial cells. In contrast, blocking connexin-43 gap junction formation had no effect on cytoplasmic transfer. All MSC populations donated mitochondria to bronchial epithelial cells with similar efficiency. Mitochondrial transfer was reduced in all co-cultures after microtubule/TNT or endocytosis inhibition. Gap junction formation inhibition reduced mitochondrial transfer in BM-MSC and BAL-MSC co-cultures but had no effect on transfer in LT-MSC co-cultures. Connexin-43 inhibition did not impact mitochondrial transfer. Finally, bronchial epithelial cells were incapable of donating cytoplasmic content or mitochondria to any MSC population. Conclusion Similar to their bone marrow counterparts, LT-MSCs and BAL-MSCs can donate cytoplasmic content and mitochondria to bronchial epithelial cells via multiple mechanisms. Given that BM-MSCs utilize these mechanisms to mediate the repair of damaged bronchial epithelial cells, both LT-MSCs and BAL-MSCs will probably function similarly.